2007
DOI: 10.1088/0957-4484/18/41/415301
|View full text |Cite
|
Sign up to set email alerts
|

Total internal reflection sum-frequency generation spectroscopy and dense gold nanoparticles monolayer: a route for probing adsorbed molecules

Abstract: We show that sum-frequency generation spectroscopy performed in the total internal reflection configuration (TIR–SFG) combined with a dense gold nanoparticles monolayer allows us to study, with an excellent signal to noise ratio and high signal to background ratio, the conformation of adsorbed molecules. Dodecanethiol (DDT) was used as probe molecules in order to assess the potentialities of the approach. An enhancement of more than one order of magnitude of the SFG signals arising from the adsorbed species is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 48 publications
1
65
1
1
Order By: Relevance
“…Therefore, the main advantage of this technique for nanotechnological devices characterization lies in its interface intrinsic molecular sensitivity at the sub-monolayer level and its potential coupling to the SPR resonance as recently demonstrated by considering samples based on solid substrate as platforms for nanosensors, an amplification factor of the molecular SFG signal was put in evidence for functionalized AuNps films with respect to a flat gold reference surface. AuNps were deposited either on silicon in external reflection configuration [4] or on glass substrates in total internal reflection configuration [5] to compare the sensitivity and molecular ordering of functionalized AuNp films as a function of the surface coverage on glass [6], to unravel the orientation of grafted molecules on AuNps and AgNps [7] and to extract and deduce the nature of the vibration modes thanks to the SPR amplification on functionalized AuNp films in the fingerprint spectral range of aromatic molecules with density functional theory (DFT) calculations [8]. In a general way, SFG has also proven its efficiency in biomolecular recognition on glass substrate [9], in DNAbased biosensors on Pt(111) single crystal [10] and in enlightening DNA hybridization on glass [11] and (100)-facetted gold films [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the main advantage of this technique for nanotechnological devices characterization lies in its interface intrinsic molecular sensitivity at the sub-monolayer level and its potential coupling to the SPR resonance as recently demonstrated by considering samples based on solid substrate as platforms for nanosensors, an amplification factor of the molecular SFG signal was put in evidence for functionalized AuNps films with respect to a flat gold reference surface. AuNps were deposited either on silicon in external reflection configuration [4] or on glass substrates in total internal reflection configuration [5] to compare the sensitivity and molecular ordering of functionalized AuNp films as a function of the surface coverage on glass [6], to unravel the orientation of grafted molecules on AuNps and AgNps [7] and to extract and deduce the nature of the vibration modes thanks to the SPR amplification on functionalized AuNp films in the fingerprint spectral range of aromatic molecules with density functional theory (DFT) calculations [8]. In a general way, SFG has also proven its efficiency in biomolecular recognition on glass substrate [9], in DNAbased biosensors on Pt(111) single crystal [10] and in enlightening DNA hybridization on glass [11] and (100)-facetted gold films [12].…”
Section: Introductionmentioning
confidence: 99%
“…37,38,55,[79][80][81] The small methylene SFG intensities observed for duration over 200 ms suggest a chain structure close to the crystallike centrosymmetric one. However, degradations (and disorder) in the alkyl chain conformation occur for a printing duration smaller than 200 ms.…”
Section: Resultsmentioning
confidence: 99%
“…However, these techniques cannot simultaneously fulfill the need to selectively monitor the molecular details of the surface and interface and avoid the interference of the information from species in the bulk. Specifically, although FT-IRRAS and SERS have the capability to probe surface chemistry with molecular resolution, FT-IRRAS generally requires a reference spectrum in order to sort out the interfacial signal and SERS needs specially prepared metal surfaces or the use of nanoparticles of the order of several nanometers to 100 nm for electromagnetic and/or chemical enhancement [159]. One surface-specific technique that has been proven to yield molecular level structure information (e.g.…”
Section: Sfg Vibrational Spectroscopymentioning
confidence: 99%
“…Recent studies have demonstrated that SFG is a powerful and information-rich probe of nanostructured surfaces [193][194][195], and surface behaviors with nanoparticles [159,[196][197][198][199][200]. In the following sections, recent advancements that explore the utility of SFG as a powerful and unique technique to study surfaces/interfaces containing nanoparticles will be covered.…”
Section: Sfg Studies At the Nano-bio Interfacementioning
confidence: 99%
See 1 more Smart Citation